Progress in experimental personality research. - Maher, Brendan A. (Brendan Arnold) 1924-.; Maher, Winifred B. (New York Academic Press, 1964)
Irregular
Editors: 1964-1979: Brendan A. Maher; 1980-1986: Brendan A. Maher and Winifred B. Maher.
Keywords: Personality -- Periodicals; Personality Disorders -- Yearbooks; Psychology, Experimental -- Yearbooks